Doric pillars at Town Hall - Ghosh, Ayan (2023)
The western entrance to the Town Hall is supported by eight columns of the Doric order. The Doric order was one of three orders of ancient Greek (and later Roman) architecture; the other two canonical orders were Ionic and Corinthian. The Doric order was fluted or smooth-surfaced, and had no base, dropping straight into the platform on which it stood.